An Empirical Comparison of a Traditional Strategy and Network Scale-Up Method for Prevalence Estimation of Child Trafficking in Sierra Leone - Yi, Hui (Crime & delinquency, 2025)
The goal of this paper is to compare a traditional survey method with the network scale-up method (NSUM) for the prevalence estimation of child trafficking in Sierra Leone in 2020. The traditional survey method involved a probability-based, stratified, and clustered multistage sampling design in which adult respondents in 3,070 households were interviewed about trafficking of children who reside in their household in three selected districts. This paper details the first attempt to estimate the prevalence of child trafficking using NSUM, which entailed questioning the same adult respondents about the trafficking-related activities of children in their personal networks. Findings and interpretation of these results are presented, along with implications and recommendations for future studies.